PEMENUHAN HAK RESTITUSI TERHADAP ANAK KORBAN TINDAK PIDANA EKSPLOITASI EKONOMI DAN SEKSUAL - Wahyu Rida Setyani; Kristiyadi Kristiyadi (Sebelas Maret University, 2021)
This article analyzes the fulfillment of the right of restitution for child victims who are victims of criminal acts of economic and sexual exploitation. The purpose of this article is to find out the fulfillment of the right of restitution for victims of the crime of economic and sexual exploitation of children based on the study of decision number: 331/Pid.Sus/2021/PN Yyk. This article is a normative legal research with a prescriptive nature and uses primary and secondary legal materials. The technique for collecting legal materials is to use a literature study with a case approach. The analysis technique used is the syllogistic method using a deductive mindset. The results of the research show that the victim's child gets the fulfillment of the right of restitution in the amount of IDR 81,650,000.-. The Yogykarta District Court judge's decision has an element of legal certainty, because the charges that have been put forward before the trial are proven legally and convincingly for the judge in making his decision. The judge's decision also reflects a sense of justice, it is said that because of the impact it has on the victim, namely the victim has to pay for medical treatment and the psychological impact has been balanced by a criminal decision that has stipulated the granting of restitution to the victim's child.Keyword: Exploitation; Restitution; Victim